Pengaruh Brand Image terhadap Keputusan Pembelian melalui Brand Trust Sebagai Variabel Mediasi pada Produk Skincare Lokal - Diva Aurellia; Helena Sidharta (Jurnal Performa)
Abstract: The purpose of this research that is done is to find out the influence of brand image on purchase decision through brand trust as mediation variable of local skincare products. This research will discuss local skincare using quantitative approach with questionnaire data collection method through google form. In order to collect research data, 90 questionnaires are distributed to respondents who are 17 to 25 years old, domicile in Surabaya, and local skincare users. Sampling is done with purposive sampling method. The measurement model in this research is analyzed by using SmartPLS 3.0 application. Analysis method that is used is Partial Least Square (PLS) which consists of outer model, that is, validity and reliability test, and inner model that examines R-square, F effect size test, path coefficient test, bootstrap, and specific indirect effects. Based on the test result of Partial Least Square (PLS) that is done, it shows that brand image variable gets the result that influences positive significant on brand trust, while brand image variable gets the result that does not have influence on purchase decision. Brand trust variable gets the result that influences positive significant on purchase decision, and brand trust variable that is also obtained the result that influences positive significant in mediating the relation of brand image on purchase decision. All variables and the relation are related to local skincare in Surabaya. This research is expected can be useful for local skincare brand companies and for future researchers are expected to be able to use other variables that can influence purchase decision variable to obtain wider result.